Implications of Changes in the Criminal Procedure Law of the ITE Law on Individual Rights in the Indonesian Legal System - Sidiq, Fahmi; Azahra, Astrid Sulistya; Pirdaus, Dede Irman (Communication in Research and Publications (CRP), 2024)
The revision of the Electronic Information and Transactions Law (UU ITE) in Indonesia has become a hot topic of debate. Institutions and activists such as the Institute for Criminal Justice Reform (ICJR) and the Press Legal Aid Institute (LBH Pers) have presented various arguments regarding the impact of these changes. This article outlines the five main arguments advanced by the ICJR and LBH Pers. First, there is an objection to Article 27 paragraph (3) which regulates insults and defamation. Second, changes in criminal procedural law raise concerns about the discretionary authority of law enforcement officials without involving the courts. Third, the addition of cyberbullying-related crimes raises concerns about the potential for over-criminalization. Fourth, governments are given additional powers to filter and block content, which can result in potential abuse. Finally, the fifth argument relates to the